Text under portrait: "A socialist and antiwar alternative to the Democratic and Republican parties: Judy White, SWP candidate for governor of New York in 1966, speaking at a Boston antiwar rally". From: Young Socialist, June 1967 (1967)
Text under portrait: "A socialist and antiwar alternative to the Democratic and Republican parties: Judy White, SWP candidate for governor of New York in 1966, speaking at a Boston antiwar rally". From: Young Socialist, June 1967.